2004
DOI: 10.1242/jeb.01040
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical energy in toddler gait A trade-off between economy and stability?

Abstract: During walking metabolic energy is consumed, even if the average walking speed is constant and there is no net change in height of the body. Energy is lost at each step and has to be put into the system again. The total amount of positive muscle-tendon work that has to be performed can be divided into two categories: external work and internal work.External work (Wext) is the amount of work performed to lift and accelerate the centre of mass. To minimize Wext adults make use of an imperfect inverted pendulum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 18 publications
2
47
1
Order By: Relevance
“…Both the normalised speed (Froude number), the correlation coefficient between E k and E p and energy recovery increased with age, but 1-5 months after the onset of independent walking they were still lower than these values in adults or in older children (Fig.·5). The recovery of mechanical energy for this age group (1-5 months after the onset of independent walking) was similar to that reported by Hallemans et al (2004).…”
Section: Relation With Speedsupporting
confidence: 89%
See 1 more Smart Citation
“…Both the normalised speed (Froude number), the correlation coefficient between E k and E p and energy recovery increased with age, but 1-5 months after the onset of independent walking they were still lower than these values in adults or in older children (Fig.·5). The recovery of mechanical energy for this age group (1-5 months after the onset of independent walking) was similar to that reported by Hallemans et al (2004).…”
Section: Relation With Speedsupporting
confidence: 89%
“…Or is it acquired with walking experience in the developing child? Previous studies have demonstrated conclusively that the mechanics of walking of children 2-12 years old, in particular the pendular recovery of energy at each step, is very similar to that of the adults when the walking speed is normalised with the Froude number (Bastien et al, 2003;Cavagna et al, 1983;Schepens et al, 2004), though in younger children (from 2 weeks to 6 months after the onset of independent walking) the mechanical energy exchange occurs to a lesser degree (Hallemans et al, 2004). However, to the best of our knowledge, the pendulum mechanism has not been investigated in toddlers who are just beginning independent, unsupported locomotion, roughly around 1 year of age.…”
mentioning
confidence: 95%
“…During that time, toddlers experience a new task and discover how to control many components through practice (Bril & Brenière;Thelen & Ulrich, 1991). As a result, many parameters stabilize, including intralimb coordination, interlimb coordination, and speed (Bril & Brenière;Clark & Phillips, 1993;Hallemans et al, 2004;Ivanenko et al, 2004). So, why might step width become less stable as step length stabilizes?…”
Section: Discussionmentioning
confidence: 99%
“…By 5 months of walking experience, toddlers have combined the postural requirements for remaining upright with forward progression, leading to a decrease in step width and in lateral acceleration of the center of mass (Bril & Brenière, 1992). By 2−4 months after the onset of independent walking, toddlers begin to use their legs effectively as inverted pendulums (Hallemans, Aerts, Otten, De Deyn, & De Clercq, 2004;Ivanenko et al, 2004). That observation implies that the rhythmic pendular oscillations seen in adult walking are not innate and that before that pattern can emerge, active neural control and intersegmental coordination are required (Ivanenko et al).…”
mentioning
confidence: 99%
“…The ground reaction forces are used to calculate the fluctuations of the centre of mass via the procedure first described in 1975 (Cavagna, 1975), and which has been applied in a large number of recent publications (Farley and Ko, 1997;Roberts and Scales, 2002;Ahn et al, 2004;Griffin et al, 2004;Hallemans et al, 2004;Parchman et al, 2003). In this method, body mass is obtained by integration of the total vertical force (of both hind limbs) over stride duration.…”
Section: Centre Of Mass (Com) Excursionsmentioning
confidence: 99%